Diseño de una biopelícula a partir de un biopolímero almidón de Manihot Esculenta “ yuca” para la liberación de fármacos -sulfonamidas en cavidad oral (2020)
The present experimental study had two phases where the objective was to design a biopolymeric system as a therapeutic alternative against resistant infections based on Manihot Esculenta-cassava starch added with drugs belonging to the select group of broad-spectrum antibiotics derived from sulfonamides- (sulfadiazine , sulfamerazine and sulfamethazine); and on the other hand to evaluate the physicochemical characteristics and the behavior that this therapeutic alternative presents